Comparison of clockwise and counterclockwise right atrial flutter using high‐resolution mapping and automated velocity measurements. - Yvorel, Cedric; Da Costa, Antoine; Lerebours, Chloe; Guichard, Jean B.; Viallon, Gregory; Romeyer, Cécile; Ferreira, Thomas; Benali, Karim; Isaaz, Karl (Journal of Cardiovascular Electrophysiology, 2021)
Background: Only few studies have been performed that explore the electrophysiological differences between clockwise (CW) and counterclockwise (CCW) right atrial (RA) cavotricuspid isthmus (CTI)‐dependent atrial flutter (AFL) using the high‐resolution Rhythmia mapping system. Objectives: We sought to compare CW and CCW CTI‐dependent AFL in pure right AFL patients (pts) using the ultra‐high‐definition (ultra‐HD) Rhythmia mapping system and we mathematically developed a cartography model based on automatic velocity RA measurements to identify electrophysiological AFL specificities. Methods and Results: Thirty‐three pts were recruited. The mean age was 71 ± 13 years old. The sinus venosus (SV) block line was present in 32/33 of cases (97%) and no significant difference was found between CCW and CW CTI AFL (100% vs. 91%; p =.7). No line was localized in the region of the crista terminalis (CT). A superior gap was present in the posterior line in 14/31 (45.2%) but this was similarly present in CCW AFL, when compared to CW AFL (10/22 [45.5%] vs. 4/10 [40%]; p =.9). When present, the extension of the posterior line of block was observed in 18/31 pts (58%) without significant differences between CCW and CW CI AFL (12/22 [54.5%] vs. 6/10 [60%]; p =.9) The Eustachian ridge line of block was similarly present in both groups (82% [18/22] vs. 45.5% [5/11]; p =.2). The absence of the Eustachian ridge line of block led to significantly slowed velocity in this area (28 ± 10 cm/s; n = 8), and the velocities were similarly altered between both groups (26 ± 10 [4/22] vs. 29.8 ± 11 cm/s [4/11]; p =.6). We created mathematical, three‐dimensional RA reconstruction‐velocity model measurements. In each block localization, when the block line was absent, velocity was significantly slowed (≤20 cm/s). A systematic slowdown in conduction velocity was observed at the entrance and exit of the CTI in 100% of cases. This alteration to the conduction entrance was localized at the lateral side of the CTI for the CCW AFL and at the septal side of the CTI for CW AFL. The exit‐conduction alteration was localized at the CTI septal side for the CCW AFL and at the CTI lateral side for the CW AFL. Conclusion: The ultra‐HD Rhythmia mapping system confirmed the absence of significant electrophysiological differences between CCW and CW AFL. The mechanistic posterior SV and Eustachian ridge block lines were confirmed in each arrhythmia. A systematic slowing down at the entrance and exit of the CTI was demonstrated in both CCW and CW AFL, but in reverse positions.